Genocide and the politics of memory : studying death to preserve life - Hirsch, Herbert, 1941- (University of North Carolina Press, 1995)
A study into repetitions of large-scale human violence throughout history. It suggests that if we begin to understand how and why these episodes occur, we will be able to act to prevent them. To revise the politics of memory, proposals for essential reforms of the political state are made.
Keywords: Genocide.; Memory -- Social aspects.; Social conflict -- Psychological aspects.; SOCIAL SCIENCE -- Demography.; Genocide; Memory -- Social aspects; Social conflict -- Psychological aspects; Völkermord; Gedächtnis; Criminology, Penology & Juvenile Delinquency.; Social Welfare & Social Work.; Social Sciences.